Hubungan Penguasaan Kalimat Efektif dan Persepsi Siswa Terhadap Cara Mengajar Guru dengan Kemampuan Mengembangkan Paragraf bagi Siswa SDN Towara Sulawesi Tengah - Wolter Lapandio (Universitas Pendidikan Mandalika, 2020)
This study aims to determine the correlation between effective sentence mastery and students' perceptions of teacher teaching methods and the ability to develop paragraphs in class V SDN Towara students. This research method uses a survey method through a correlational study. The research sample was taken by proportional random sampling technique with a total of 80 students from a total population of 120 students. The research instrument used tests and questionnaires. While the data analysis technique of this study uses simple correlation techniques and multiple correlation. The results of this study indicate that effective sentence mastery and student perceptions of the way teachers teach individually or collectively have a positive relationship with the ability to develop paragraphs. If we look at the value of the independent variable's contribution to the dependent variable, it is known that effective sentence mastery gives a greater contribution or contribution than students' perceptions of the way teachers teach.